A new species of Anacroneuria Klapálek 1909 (Plecoptera: Perlidae) and notes on the altitudinal distribution of the genus in Costa Rica - Gutiérrez-Fonseca, Pablo E.; Springer, Monika (Zootaxa, 2015)
Anacroneuria is the most widespread genus of Perlidae throughout the Neotropical region and 30 species have been reported from Costa Rica. In this paper, we describe and illustrate a new species from a high elevation cloud forest, A. quetzali sp.n., increasing to 31 the number of described species for Costa Rica. In addition, we examine the altitudinal distribution of Anacroneuria in Costa Rica to determine possible patterns, using the data available on its altitudinal range (10–2700 masl). We divided the elevational range in seven categories, using 500 m intervals. We found that most species (90.3%) are distributed in elevations that range from 500 to 1500 masl, followed by low-elevations (35.5%). Interestingly, despite the fact that Plecoptera are known to inhabit clean, fast flowing water at high elevations, only 16.1% of the species have been found at high elevations in Costa Rica (above 2000 masl). Thus, it seems that most Anacroneuria species are distributed in middle elevations, which are the areas that have a high diversity of freshwater habitats.